A REVIEW ON EXOSOMES, RELATIONSHIP WITH HIV AND THERAPEUTIC PERSPECTIVES (International Journal of Food and Nutritional Sciences, 2019)
As small nanosized particles released from cells by exocytosis, exosomes have beenrecognized as significant modulators in intercellular communication. Henceforth, it isimportant to note that these extracellular vesicles may inhibit or enhance viral infection frominfected to uninfected ones, thus playing an important role in HIV progression